3D microstructure analysis of silicon–boron phosphide mixed nanocrystals. Issue 13 (20th March 2020) - Nomoto, Keita; Sugimoto, Hiroshi; Ceguerra, Anna V.; Fujii, Minoru; Ringer, Simon P.
Abstract : Microstructure study of boron (B) and phosphorus (P) codoped silicon (Si) nanocrystals (NCs), cubic boron phosphide (BP) NCs and their mixed NCs (B x Si y P z NCs). Abstract : The microstructure of boron (B) and phosphorus (P) codoped silicon (Si) nanocrystals (NCs), cubic boron phosphide (BP) NCs and their mixed NCs (B x Si y P z NCs) has been studied using atom probe tomography (APT), transmission electron microscopy (TEM), and Raman scattering spectroscopy. The B x Si y P z NCs inherit superior properties of B and P codoped Si NCs such as high dispersibility in aqueous media and near infrared (NIR) luminescence and those of cubic BP NCs such as high chemical stability. The microanalyses revealed that B x Si y P z NCs are composed of a crystalline core and an amorphous shell. The core possesses a lattice constant between that of Si (diamond-cubic) and BP (cubic). The amorphous shell is comprised of B, Si and P, though the composition is not uniform and there are local B-rich, Si-rich and P-rich domains connected contiguously. The amorphous shell is proposed to be responsible for their superior chemical properties such as high dispersibility in polar solvents and high resistance to acids, and the crystalline core is responsible for the stable NIR luminescence.